Digital Financial Inclusion and the Level of Financial Development - Arsov, Sasho; Nedanovski, Pece; Naumoski, Aleksandar (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2025)
The paper explores the issue of digital financial inclusion as a means to overcome the traditional hurdles in access to financial services and its impact on the level of financial development. Using a broad sample of 102 countries worldwide and a time series of data ranging from 2011 to 2021, a Principal Component Analysis is applied to derive a single measure of digital financial inclusion (DFI). The ranking shows that the developed countries and the European nations in general dominate the list, while the bottom is mostly populated by African countries. Using a modified digital financial inclusion index to meet the availability of data, a regression analysis using OLS and GMM techniques was applied to determine the impact of DFI on the level of financial development. The results show that digital financial inclusion has a positive impact on financial development, so the authorities should closely monitor and support the use of digital technologies in the financial sector, as well as enhance the access of the population to these opportunities and their ability to use modern communication technologies.
Keywords: Financial development; Digital financial inclusion; Debit card; ATM